Spinning boson stars and Kerr black holes with scalar hair: the effect of self-interactions - Herdeiro, Carlos A. R. (2016)
Self-interacting boson stars (BSs) have been shown to alleviate the astrophysically low maximal mass of their nonself-interacting counterparts. We report some physical features of spinning self-interacting BSs, namely their compactness, the occurrence of ergo-regions and the scalar field profiles, for a sample of values of the coupling parameter. The results agree with the general picture that these BSs are comparatively less compact than the nonself-interacting ones. We also briefly discuss the effect of scalar self-interactions on the properties of Kerr black holes with scalar hair.